The 'regulatory grey zone': bylaw enforcement's governing of homelessness and space. - Martino, Natasha; Sanders, C. B.; Dej, E. (Policing & Society, 2024)
Over the past two decades, homelessness has become more visible, and with it are increased demands for law enforcement to minimise the visibility of people experiencing homelessness, and manage, or ultimately remove, local encampments. While scholarship exists on police responses to homelessness, the role that other security actors, such as municipal bylaw officers, play in managing and regulating homelessness is largely unknown. In this paper, we explore municipal bylaw officers' perceptions of their roles and responsibilities related to homelessness in Ontario, Canada. Our analysis reveals how bylaw officers have become important players in the security governance of homelessness. We demonstrate how bylaw officers' policies, which focus on the regulation of space, are loosely coupled with, or disconnected from, their frontline activities, which require the regulation of people. This loose coupling situates bylaw officers in a perceived regulatory grey zone, requiring them to use discretionary solutions informed by their subjective experiences to govern people experiencing homelessness. The reliance on subjectivity and discretion expands security networks regulating and governing people experiencing homelessness.